2017
DOI: 10.35790/ecl.5.2.2017.18540
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Faktor Risiko Penderita Osteoartritis Lutut di Instalasi Rehabilitasi Medik RSUP Prof. Dr. R. D. Kandou Manado Periode Januari –Juni 2017

Abstract: Osteoarthritis (OA) is a chronically progressive degenerative joint disease associated with joint cartilage damage. It is usually affected the joints of the hands, vertebrae, hips, and knee which is reported as the most common affected location. Risk factors of OA are divided into non-modifiable factors and modifiable factors. The non-modifiable risk factors are age, gender, race, and genetic factors, while the modifiable factors are body mass index, occupation, knee injury, blood pressure, blood sugar level, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 9 publications
0
3
0
7
Order By: Relevance
“…Kandou Manado in January -June 2017 also showed that knee osteoarthritis patients' characteristic was dominated by elderly (66.7%), and female (70.4%). 7 Silverwood et al had summarized 11 cohort studies which showed that females have greater risk factors for osteoarthritis. 8 There are anatomical and hormonal differences between males and females which were related to the volume of the knee cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Kandou Manado in January -June 2017 also showed that knee osteoarthritis patients' characteristic was dominated by elderly (66.7%), and female (70.4%). 7 Silverwood et al had summarized 11 cohort studies which showed that females have greater risk factors for osteoarthritis. 8 There are anatomical and hormonal differences between males and females which were related to the volume of the knee cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini juga sejalan dengan penelitian pada Poli Rehabilitasi Medik RS. Kandou Manado menunjukkan sebanyak 66.6% pasien OA genu yang berkunjung ke Poli rehab medik pada tahun 2017 merupakan kelompok usia >60 tahun (13). Namun, Pada penelitian yang dilakukan di Pelayanan Rehabilitasi Medik RSIJ Pondok Kopi didapatkan proporsi kelompok usia terbesar pasien OA genu adalah rentang usia diatas 65 tahun yaitu sebesar 38,8% (Adani, et al, 2020).…”
Section: Pembahasan Karakteristik Usiaunclassified
“…Pada penelitian sejenis di RSUP. Prof. Kandou Manado kelompok pekerjaan terbesar merupakan pensiunan (80,9%) (13). Pada studi crosssectional skala nasional di Korea selatan didapatkan pekerjaan manajerial, termasuk pekerjaan kantor dan pekerjaan pelayanan, memiliki prevalensi OA lutut terendah.…”
Section: Karakteristik Pekerjaanunclassified
“…Sebagian besar subjek penelitian merupakan pensiunan dengan persentase sebesar 32%. Hal ini sejalan dengan penelitian yang dilakukan oleh Soeryadi et al (2017) dengan hasil bahwa sebesar 51,9% pasien OA lutut merupakan pensiunan dan sebesar 18,5% merupakan IRT. Penelitian yang dilakukan oleh Kiadaliri et al (2016) juga mendapatkan hasil bahwa sekitar 80,9% penderita OA merupakan pensiunan.…”
Section: Pembahasanunclassified